2019
DOI: 10.7759/cureus.4552
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Overall Survival in Patients With Multiple Primary Malignancies: A Single-center Experience

Abstract: Introduction Multiple primary malignancies (MPMs) are seen in ~5% of all tumors. The aim of this study was to determine the quantitative impact on overall survival (OS) and treatment choices in patients with MPMs. Methods A retrospective analysis to determine patients with MPMs was conducted over a six-year period. Patients were defined as simultaneous MPMs if the second malignancy was discovered within 60 days of the first, and as sequential MPMs if discovered after 60 days of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Research has shown that synchronous MPMs are associated with a significant reduction in overall survival in comparison to metasynchronous malignant tumors [16]. Nevertheless, the prognosis of such medical conditions is very variable and mainly determined by the outcome of the most aggressive tumor [14].…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that synchronous MPMs are associated with a significant reduction in overall survival in comparison to metasynchronous malignant tumors [16]. Nevertheless, the prognosis of such medical conditions is very variable and mainly determined by the outcome of the most aggressive tumor [14].…”
Section: Discussionmentioning
confidence: 99%
“…MPTs are classified as synchronous or metachronous whether the diagnosis interval between the first and second tumors is less or greater than 6 months, respectively [ 44 ]. Among the epidemiological factors related to the development of MPTs, tobacco exposure has been described as one of the most determining and commonly shared risk factors in several studies [ 44 , 45 ]. Patients with MPTs have the worst prognosis compared to those with a single neoplasm, and among these, synchronous neoplasms present a statistically significant decrease in mOS when compared with the metachronous ones, given the fact that their faster development (<6 months) implies a more aggressive component of the disease [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the epidemiological factors related to the development of MPTs, tobacco exposure has been described as one of the most determining and commonly shared risk factors in several studies [ 44 , 45 ]. Patients with MPTs have the worst prognosis compared to those with a single neoplasm, and among these, synchronous neoplasms present a statistically significant decrease in mOS when compared with the metachronous ones, given the fact that their faster development (<6 months) implies a more aggressive component of the disease [ 45 ]. On the contrary, the prognosis is also influenced by the simultaneous versus sequential diagnosis of MPTs (being worse if the diagnosis is sequential of >60 days), probably related to the fact that early simultaneous diagnosis correlates with earlier treatment initiation and better long-term outcomes [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the incidence of MPMs is increasing and is expected to continue to do so. This increase has been ascribed to several factors, such as better imaging detection of many forms of cancer, longer mean lifetime, mostly in Western populations, treatments at initial tumour staging, quality of oncologic follow-up, and better prognosis of many neoplasms [14][15][16]. According to the literature, 1.2-3.5% of cancer patients are unexpectedly affected by a new synchronous neoplasia detected during a diagnostic or therapeutic phase [17].…”
Section: Discussionmentioning
confidence: 99%